Functional characterization of a cycloartenol synthase and four glycosyltransferases in the biosynthesis of cycloastragenol-type astragalosides from Astragalus membranaceus - Yangyang Duan; Wenyu Du; Zhijun Song; Ridao Chen; Kebo Xie; Jimei Liu; Dawei Chen; Jungui Dai (Elsevier, 2023)
Astragalosides are the main active constituents of traditional Chinese medicine Huang-Qi, of which cycloastragenol-type glycosides are the most typical and major bioactive compounds. This kind of compounds exhibit various biological functions including cardiovascular protective, neuroprotective, etc. Owing to the limitations of natural sources and the difficulties encountered in chemical synthesis, re-engineering of biosynthetic machinery will offer an alternative and promising approach to producing astragalosides. However, the biosynthetic pathway for astragalosides remains elusive due to their complex structures and numerous reaction types and steps. Herein, guided by transcriptome and phylogenetic analyses, a cycloartenol synthase and four glycosyltransferases catalyzing the committed steps in the biosynthesis of such bioactive astragalosides were functionally characterized from Astragalus membranaceus. AmCAS1, the first reported cycloartenol synthase from Astragalus genus, is capable of catalyzing the formation of cycloartenol; AmUGT15, AmUGT14, AmUGT13, and AmUGT7 are four glycosyltransferases biochemically characterized to catalyze 3-O-xylosylation, 3-O-glucosylation, 25-O-glucosylation/O-xylosylation and 2ʹ-O-glucosylation of cycloastragenol glycosides, respectively. These findings not only clarified the crucial enzymes for the biosynthesis and the molecular basis for the structural diversity of astragalosides in Astragalus plants, also paved the way for further completely deciphering the biosynthetic pathway and constructing an artificial pathway for their efficient production.